Researching Documentary Heritage. Letters of Lithuanian Partisans - Vaitkevičius, Vykintas (Tautosakos darbai, 2025)
The article discusses letters written by the participants of the Lithuanian anti-Soviet armed resistance to their family members, loved ones, comrades-in-arms, contact persons, supporters, as well as provocateurs and Soviet collaborators. This is the first attempt at covering this unique part of the documentary heritage of the partisan war, which has survived in the archives hidden by the partisans themselves, files from the state security agency and the criminal ones, and by the families of the fighters’ relatives, and has not been researched so far. Using the method of content analysis, the author of the article examines over 400 letters written by the partisans under wartime conditions, presenting in more detail letters of farewell, concern, longing and love, news or agreements. He uses two examples to show the exceptional value of the partisan letters as historical sources. Special attention is given to the communication networks and contact persons who made the partisan mail service operational and correspondence possible. It is concluded that partisan letters in Lithuanian history and culture are war letters, or war correspondence, imbued with pain caused by separation of the freedom fighters from their families and the loved ones, as well as their concern for the living conditions and fate of the latter. However, these letters also express their determination to fight, hatred for the enemy, and love of the homeland. Although the content of many partisan letters is businesslike, they often openly reveal or imply the fragile existential situation of the freedom fighters.